If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19b + -4 = 73 Reorder the terms: -4 + 19b = 73 Solving -4 + 19b = 73 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 19b = 73 + 4 Combine like terms: -4 + 4 = 0 0 + 19b = 73 + 4 19b = 73 + 4 Combine like terms: 73 + 4 = 77 19b = 77 Divide each side by '19'. b = 4.052631579 Simplifying b = 4.052631579
| x-8.4=-4.7 | | 70=10-3x | | 48x-32=78 | | 2.1=0.3y | | 8(3x+2)=5(x+6)-5 | | 5r^4=100 | | x^4-24x^2+135=0 | | x+8(x-7)=-2(3x+1)+6x | | x^4-25x^2+135=0 | | 48x-32+28=78 | | 7z-0.3=8z | | j-21=21 | | -w+13=5w-5 | | 2w+56=176 | | 1.25x+5=-3 | | 24x=27x-6 | | -3.7y-5.7=-0.8y+3 | | 3(x+1)-2x=x+3 | | 2y+40=100 | | -4x+-9=-5-6x | | 10x+4=4x+7 | | 3(2m-4)=2m+4m-4 | | .75a+.75a+a=15 | | 9v-8(1+6v)= | | 24+2y+13=20+4y-19 | | 4(n+1)+3=-35-2n | | 3(2+r)-2r=2r+11 | | 8y-16=5y+2 | | 7(t-5)+8t=5(3t+5)-13 | | 13*k=52 | | 2x-5y+z=5 | | 5(k-2)-2(k+4)=6 |